Outcome of radial head and neck fractures with radial head replacement - Baig, Mirza A.; Kommera, Srujith; Rafai, Syed Z. (International Journal of Research in Orthopaedics, 2024)
Radial head and neck fractures are a significant concern in elbow injuries, often stemming from incidents like falls or accidents, which can severely affect elbow stability and function. This study, conducted at Shadan Institute of Medical Sciences in Hyderabad, India, focused on 15 patients with severe radial head fractures classified as Mason type III and IV. The research aimed to evaluate the effectiveness of radial head replacement utilizing implants from leading manufacturers such as DePuy Synthes® and Zimmer Biomet®. The surgical procedures were carried out successfully without any notable intraoperative complications, with an average surgery duration of 60 minutes. Postoperative complications, though relatively rare, included issues such as elbow stiffness and peri-prosthetic osteolysis, which were manageable. However, the majority of patients exhibited improved functional outcomes, as indicated by excellent Mayo elbow performance scores during the 6-month follow-up. This intervention not only enhances elbow stability but also facilitates soft tissue healing and promotes better range of motion. Consequently, radial head replacement emerges as a highly effective approach for managing severe radial head fractures, leading to considerable improvements in patient outcomes and quality of life.